Enabling Environments on a Shoestring: A Guide to Developing and Reviewing Early Years Provision - Eaton Caroline; The British Association For Early Childhood Education (London, 2014)
Introduction, Acknowledgements, Principles for an Enabling Environment, Practical Tips, Case Studies, Reviewing and Reflecting, End Words, References and Further Reading.